Analisis Persaingan Pasar, Faktor Internal dan Eksternal Bank terhadap Efesiensi Bank Syariah di Indonesia - Sahrullah, Abdul Aziz; Suprayogi, Noven (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2022)
The present study aims to analyze the efficiency of several sharia banks in Indonesia. The study also aims to analyze several other factors that may influence efficiencies, such as market competition, internal factors, and external factors. The study is conducted using a quantitative approach and analyzes the data using two different steps. The first step measures the efficiency using DEA and the second step analyzes the efficiency using data panel regression. The data is collected using purposive technique sampling and using 11 different sharia banks as the main data of the study. The study shows that ROA has a significant negative influence on the sharia bank